Strategic Factors for Building Brand Equity: Jordan Medical Tourism - Shriedeh, Fayez Bassam (Jurnal The Messenger, 2019)
Building a brand with strong equity is a vital element for differentiation and competitiveness, especially in today s highly competitive medical tourism. The literature indicated that Jordan has weak medical tourism brand equity. The contribution of customer relationship management and service quality in developing brand equity can t be ignored. Studies on marketing activities towards building brand equity remain limited. Accordingly, 650 self-administrated questionnaires were distributed to outpatient medical tourists in Amman s five biggest hospitals using systematic sampling. After screening, 454 surveys were used for analysis using structural equation modelling. The results indicated that customer relationship management significantly impacted service quality and brand equity. Service quality strongly influenced brand equity, and brand equity was enhanced indirectly through service quality. This study highlighted the importance of such factors on brand equity-building activities in Jordanian medical tourism context. Further research is recommended to expand the proposed model.